2015
DOI: 10.1186/s12885-015-1501-9
|View full text |Cite
|
Sign up to set email alerts
|

The different role of intratumoral and peritumoral lymphangiogenesis in gastric cancer progression and prognosis

Abstract: BackgroundTumor-induced lymphangiogenesis plays a crucial role in metastasis and tumor progression. However, the significance of intratumoral lymphovascular density (I-LVD) and peritumoral lymphovascular density (P-LVD) has been controversial in gastric cancer. The purpose of this study was to investigate the differences of clinicopathologic characteristics with respect to I-LVD and P-LVD in gastric cancer.MethodsSamples of I-LVD and P-LVD from 66 patients who had undergone radical gastrectomy for gastric canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 41 publications
2
23
1
Order By: Relevance
“…Our results are consistent with accumulated lines of evidence that strongly suggest the role of tumour-induced lymphangiogenesis in progression and metastasis of various cancers, i.e. prostate adenocarcinoma, oesophageal squamous cell carcinoma, gastric, breast and lung cancer (28)(29)(30)(31)(32). Considering haematological malignancies, positive correlation between increased number of PDPN-positive vessels and disease progression was reported in Sézary syndrome, the most common, aggressive CTCL (33).…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with accumulated lines of evidence that strongly suggest the role of tumour-induced lymphangiogenesis in progression and metastasis of various cancers, i.e. prostate adenocarcinoma, oesophageal squamous cell carcinoma, gastric, breast and lung cancer (28)(29)(30)(31)(32). Considering haematological malignancies, positive correlation between increased number of PDPN-positive vessels and disease progression was reported in Sézary syndrome, the most common, aggressive CTCL (33).…”
Section: Discussionsupporting
confidence: 91%
“…Watanabe et al reported that intranodal lymphatic vessel density was significantly correlated with the size of the metastasis [27]. Furthermore, peritumoral lymphovascular density was significantly increased in cases with lymph node metastasis [28]. These results suggest that the lymphatic network develops both morphologically and immunologically in cases with lymph node metastasis.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have associated I-LVD with tumor LN metastasis in head and neck squamous cell carcinoma [55,56], papillary thyroid carcinoma [58], pancreatic endocrine tumors [57], and gastric carcinoma [58].…”
Section: Discussionmentioning
confidence: 99%